A general approach to iridoids by applying a new Julia olefination and a tandem anion-radical-carbocation crossover reaction. Issue 40 (21st September 2016) - Řehová, Lucie; Dračínský, Martin; Jahn, Ullrich
Abstract : An efficient asymmetric approach to dihydronepetalactone and dolicholactone is presented featuring a Julia olefination and an anion–radical–cation crossover reaction. Abstract : A unified, asymmetric approach to the total synthesis of naturally occurring iridoids is presented. The synthesis features a recently discovered ortho → α transmetalation of alkyl aryl sulfone carbanions, thus enabling Julia reactions, by which so far hardly accessible disilylated olefins have been obtained. A subsequent tandem alkoxycarbonylation/oxidative radical cyclization afforded substituted cyclopentane building blocks with high diastereoselectivity. These compounds serve as unique central intermediates for short access to dihydronepetalactone, dolicholactone and potentially other iridoids.